Prioritizing conservation of tropical dry forests in the Pacific. Issue 3 (17th February 2014) - Gillespie, Thomas W.; O'Neill, Kristin; Keppel, Gunnar; Pau, Stephanie; Meyer, Jean-Yves; Price, Jonathan P.; Jaffré, Tanguy
Abstract: To identify forests of high priority for conservation in tropical dry forests of New Caledonia, Fiji, the Marquesas and Hawaii, we examined patterns of woody plant species richness (total, native and endemic) and threatened species (IUCN categorization and density) at the stand level, using Gentry's transect method. There were associations between total, native and endemic plant species richness in all four Pacific dry forest regions but we found no significant association with the presence or density of species listed on the IUCN Red List. Dry forests in New Caledonia and Hawaii merit the highest conservation priority in the Pacific, based on level of endemism and number of threatened species. The study sites that merit high conservation priority are Metzdorf, Nekoro and Pindai, in New Caledonia, Kokee and Kaupulehu, in Hawaii, and Vatia, in Fiji. New Caledonia and Fiji have a small dry forest extent and protected area extent compared with other dry forests in biodiversity hotspots. Although we identified priority areas for dry forest conservation, more comparative plot data, presence/absence data in fragments and regional geographical data are needed to adequately manage and protect dry forests in the Pacific.